2007
DOI: 10.1214/ejp.v12-463
|View full text |Cite
|
Sign up to set email alerts
|

Processes on Unimodular Random Networks

Abstract: We investigate unimodular random networks. Our motivations include their characterization via reversibility of an associated random walk and their similarities to unimodular quasi-transitive graphs. We extend various theorems concerning random walks, percolation, spanning forests, and amenability from the known context of unimodular quasi-transitive graphs to the more general context of unimodular random networks. We give properties of a trace associated to unimodular random networks with applications to stoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,061
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(1,072 citation statements)
references
References 82 publications
(114 reference statements)
8
1,061
0
3
Order By: Relevance
“…Let d be the degree of Cay( , S). In Aldous and Lyons [AL,10.5], the question of existence of invariant, random k-colorings is discussed and it was mentioned that Schramm (unpublished, 1997) had shown that for any , S there is an invariant, random (d + 1)-coloring (this also follows from the more general Kechris-Solecki-Todorcevic approach [KST,4.8]). They also pointed out that Brooks' theorem implies that there is an invariant, random d-coloring when is a sofic group (for the definition of sofic group, see e.g.…”
Section: T Conley Et Almentioning
confidence: 99%
“…Let d be the degree of Cay( , S). In Aldous and Lyons [AL,10.5], the question of existence of invariant, random k-colorings is discussed and it was mentioned that Schramm (unpublished, 1997) had shown that for any , S there is an invariant, random (d + 1)-coloring (this also follows from the more general Kechris-Solecki-Todorcevic approach [KST,4.8]). They also pointed out that Brooks' theorem implies that there is an invariant, random d-coloring when is a sofic group (for the definition of sofic group, see e.g.…”
Section: T Conley Et Almentioning
confidence: 99%
“…Sofic groups have been linked to theory of stochastic processes in infinite networks [3] and to cellular automation [15], and have been shown to admit a classification of their Bernoulli actions [12].…”
Section: Variamentioning
confidence: 99%
“…It is also possible to go from a stationary and reversible random graph towards a unimodular random one by biasing by deg(ρ) −1 , see [AL07,BC12].…”
Section: Stationary Along Srwmentioning
confidence: 99%
“…This is interesting, because of course it does not have translation invariance of any form. But unimodularity can replace that in many arguments, see [AL07]. How does IIC looks like on a 2 − 3-tree?…”
Section: The Incipient Infinite Cluster (Iic)mentioning
confidence: 99%